Molecular features and clinical outcomes of EGFR-mutated, MET-amplified non-small-cell lung cancer after resistance to dual-targeted therapy - Mei-Mei Fang; Jiang-Tao Cheng; Yu-Qing Chen; Xiao-Cheng Lin; Jun-Wei Su; Yi-Long Wu; Hua-Jun Chen; Jin-Ji Yang (Therapeutic Advances in Medical Oncology, 2024)
Background: Some studies of dual-targeted therapy (DTT) targeting epidermal growth factor receptor (EGFR) and mesenchymal-epithelial transition (MET) have shown promising efficacy in non-small-cell lung cancer (NSCLC). Consequently, patient management following DTT resistance has gained significance. However, the underlying resistance mechanisms and clinical outcomes in these patients remain unclear. Objectives: This study aimed to delineate the molecular characteristics and survival outcomes of patients with NSCLC harboring EGFR mutations and acquired MET amplification after developing resistance to DTT. Design: We conducted a retrospective analysis of patients with NSCLC with EGFR mutations and acquired MET amplification who exhibited resistance to EGFR/MET DTT. Methods: Next-generation sequencing (NGS) was performed on patients with available tissue samples before and/or after the development of resistance to DTT. Stratified analyses were carried out based on data sources and subsequent salvage treatments. Univariate/multivariate Cox regression models and survival analyses were employed to explore potential independent prognostic factors. Results: The study included 77 NSCLC patients, with NGS conducted on 19 patients. We observed many resistance mechanisms, including EGFR-dependent pathways (4/19, 21.1%), MET-dependent pathways (2/19, 10.5%), EGFR/MET co-dependent pathways (2/19, 10.5%), and EGFR/MET-independent resistance mechanisms (11/19, 57.9%). Post-progression progression-free survival (pPFS) and post-progression overall survival (pOS) significantly varied among patients who received the best supportive care (BSC), targeted therapy, or chemotherapy (CT), with median pPFS of 1.5, 3.9, and 4.9 months, respectively ( p  = 0.003). Median pOS were 2.3, 7.7, and 9.2 months, respectively ( p  < 0.001). The number of treatment lines following DTT resistance and the Eastern Cooperative Oncology Group performance status emerged as the independent prognostic factors. Conclusion: This study revealed a heterogeneous landscape of resistance mechanisms to EGFR/MET DTT, with a similar prevalence of on- and off-target mechanisms. Targeted therapy or CT, as compared to BSC, exhibited the potential to improve survival outcomes for patients with advanced NSCLC following resistance to DTT.